Cross-Cultural Parenting Practices in Dutch-Indonesian Intercultural Families: Perspectives on Child-Rearing Between Individualism and Collectivism - Marleen Verhoeckx (South Sulawesi Education Development (SSED), 2026)
Purpose: Intercultural marriages between Dutch and Indonesian partners represent a culturally significant yet underexplored configuration in cross-cultural parenting scholarship. This study examines how individualistic Dutch and collectivistic Lombok-Indonesian cultural values shape divergent child-rearing practices, and how an intercultural parent navigates and negotiates these differences in everyday family life. The study is motivated by the near-absence of qualitative research on Dutch-Indonesian intercultural families and the lack of scholarly attention to Lombok-Sasak parenting practices in the international literature. Methodology: A qualitative narrative inquiry approach was employed, drawing on the lived experience of Marleen Verhoeckx, a Dutch social worker with professional specialization in mental health, a year-long government-funded immersion in Indonesian culture and language (Darma Siswa scholarship), and sustained parenting experience within a Dutch-Lombok intercultural household. Data were generated through in-depth narrative reflection and analyzed thematically using Hofstede's individualism-collectivism framework and Greenfield et al.'s cultural pathways theory as guiding analytical lenses. Results: Seven thematic dimensions of cross-cultural parenting difference were identified: sleep arrangements, postnatal support structures, birth rituals, physical contact norms, responses to infant distress, parental decision-making, and gender roles. Dutch parenting was characterized by early infant sleep independence, professional kraamzorg postnatal care, reflective responses to child distress, egalitarian co-parenting, and shared gender roles. Lombok-Indonesian parenting was characterized by mother-infant co-sleeping, family and dukun bayi-based postnatal support, the medaq au birth naming ceremony, communal infant engagement, immediate gratification of infant distress, authority-based decision-making, and gender-differentiated caregiving roles Conclusions: The findings reveal a coherent and systematic alignment between Dutch parenting practices and individualistic cultural values, and between Lombok-Indonesian practices and collectivistic cultural values, extending Hofstede's framework into the specific Dutch-Indonesian intercultural context. This study contributes ethnographically specific knowledge about Lombok-Sasak child-rearing to the cross-cultural early childhood literature and offers practical insights for social workers, family counselors, and early childhood practitioners supporting intercultural families. The findings underscore the importance of cultural humility in professional practice and call for future research incorporating multiple participants and longitudinal perspectives.